2004
DOI: 10.1097/00000478-200407000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Pathologically and Biologically Distinct Types of Epithelium in Intraductal Papillary Mucinous Neoplasms

Abstract: Although general characteristics of intraductal papillary mucinous neoplasms (IPMNs) and their delineation from other pancreatic tumors have been well established, several issues regarding their biology and management remain unresolved. It has been noted briefly by us and other authors that there are different types of papillae in IPMNs; however, their frequency, biologic significance, and clinical relevance are unknown. In this study, the association of different papillary patterns with clinical, pathologic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
369
0
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(398 citation statements)
references
References 48 publications
18
369
0
11
Order By: Relevance
“…Gastric types usually showed mild dysplasia and intestinal types showed moderate to severe dysplasia, whereas pancreatobiliary and oncocytic types showed severe dysplasia corresponding to carcinoma in situ; 8,10,14 intestinal-type neoplasms were more frequently associated with a mucinous noncystic (colloid) invasive pattern compared with other types; 4,7-9,12 and the oncocytic type was a rare variant. 46 With regard to the relationship between fascin expression and the phenotypic subclassification, fascin overexpression occurred more frequently in intestinal-type neoplasms (90%) than in the gastric type (61%) by multiple comparisons.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Gastric types usually showed mild dysplasia and intestinal types showed moderate to severe dysplasia, whereas pancreatobiliary and oncocytic types showed severe dysplasia corresponding to carcinoma in situ; 8,10,14 intestinal-type neoplasms were more frequently associated with a mucinous noncystic (colloid) invasive pattern compared with other types; 4,7-9,12 and the oncocytic type was a rare variant. 46 With regard to the relationship between fascin expression and the phenotypic subclassification, fascin overexpression occurred more frequently in intestinal-type neoplasms (90%) than in the gastric type (61%) by multiple comparisons.…”
Section: Discussionmentioning
confidence: 93%
“…[7][8][9][10][11][12][13] Recently, a consensus on the subclassification of IPMNs was agreed among international experts on pancreatic precursor lesions, and published. 14 Subclassification makes it easier to compare studies among different institutions and understand the biological behavior, and is essential for future studies of IPMN.…”
mentioning
confidence: 99%
“…30 Recently, Sadakari and coworkers 3 have shown that invasive carcinoma derived from the non-intestinal-type intraductal papillary mucinous neoplasm has a poorer prognosis than that derived from the intestinal type. Previous studies have identified markers specific for intestinal-type intraductal papillary mucinous neoplasm, including MUC2, CDX2, and REG4.…”
Section: Discussionmentioning
confidence: 99%
“…Intraductal papillary-mucinous neoplasms of branch-duct type can be distinguished from ductal adenocarcinomas by their frequent positivity for MUC5AC and negativity for MUC1. 36 In summary, pancreatic ductal adenocarcinomas and their variants with cystic features are neither rare, nor do they form a uniform group. Instead, they occur in a considerable percentage of cases and show a spectrum of cystic changes ranging from neoplastic to non-neoplastic structures, each showing special features and its own pathogenesis.…”
Section: Discussionmentioning
confidence: 99%